Complement Activation by C-Reactive Protein Is Critical for Protection of Mice Against Pneumococcal Infection - Singh, Sanjay K.; Ngwa, Donald N.; Agrawal, Alok (Frontiers in Immunology, 2020)
C-reactive protein (CRP), a component of the innate immune system, is an antipneumococcal plasma protein. Human CRP has been shown to protect mice against infection with lethal doses of Streptococcus pneumoniae by decreasing bacteremia. In vitro, CRP binds to phosphocholine-containing substances, such as pneumococcal C-polysaccharide, in a Ca2+-dependent manner. Phosphocholine-complexed human CRP activates the complement system in both human and murine sera. The mechanism of antipneumococcal action of CRP in vivo, however, has not been defined yet. In this study, we tested a decades-old hypothesis that the complement-activating property of phosphocholine-complexed CRP contributes to protection of mice against pneumococcal infection. Our approach was to investigate a CRP mutant, incapable of activating murine complement, in mouse protection experiments. We employed site-directed mutagenesis of CRP, guided by its three-dimensional structure, and identified a mutant H38R which, unlike wild-type CRP, did not activate complement in murine serum. Substitution of His38 with Arg in CRP did not affect the pentameric structure of CRP, did not affect the binding of CRP to pneumococci, and did not decrease the stability of CRP in mouse circulation. Employing a murine model of pneumococcal infection, we found that passively administered H38R CRP failed to protect mice against infection. Infected mice injected with H38R CRP showed no reduction in bacteremia and did not survive longer, as opposed to infected mice treated with wild-type CRP. Thus, the hypothesis that complement activation by phosphocholine-complexed CRP is an antipneumococcal effector function was supported. We can conclude now that complement activation by phosphocholine-complexed CRP is indeed essential for CRP-mediated protection of mice against pneumococcal infection.